Probable occurrence of "cristacortis" in citron (Citrus medica L.) At the south of Minas Gerais, Brazil - Gonçalves, Neide Botrel; Fortes, Lucimar de A.; Auras, Nátia E.; Barrios, Soraya C.; Peixoto, Paulo H. P; Rezende, Leila de P.; Godinho, Francisco de P. (Pesquisa Agropecuaria Brasileira, 1991)
The occurrence of symptoms looking like Cristacortis virous, in a Cidreira Diamante (Citrus medica. L.), cultivar in the orchard of Escola Superior de Agricultura de Lavras - ESAL -, in Lavras, MG, Brazil, was observed. More studies may be conduced for clearing up this observation, in order to avoid possible dissemination.